Fretting Fatigue Damage Nucleation and Propagation Lifetime Using a Central Point Movement of Power Spectral Density - Thanh Q. Nguyen; Hieu C. Doan; Luan C. Vuong; H. Nguyen-Xuan; Nhi K. Ngo (Shock and Vibration)
This paper presents a new perception in evaluating fretting fatigue damage nucleation and propagation lifetime under periodically forced circulation. A new approach, which is proposed in this paper, is to measure the change of the central point of power spectral density (CP-PSD) in different structural stiffness degradation stages. A notable aspect of this study lies in the combination between vibration amplitude and forced frequency of the fatigue-causing factors in beam structures. Additionally, it is found that randomization of the first phase from 0 to 2π yields more accurate modelling of the fatigue phenomenon. Results show that the CP-PSD parameter is significantly more sensitive compared to the regularly damage-evaluating parameters such as natural frequency, eigenvalues, or stress value. This reflects different levels of fatigue cycle effect on the structure in the experiment. At the same time, CP-PSD also categorizes the degradation level on different points on the structure under the periodically forced circulation. In addition, this paper also quantifies the relation between the changes of CP-PSD and each fatigue state. Results of this research will be a reference source to evaluate the lifespan of the structure by experimental methods.